2018
DOI: 10.11114/jets.v7i1.3758
|View full text |Cite
|
Sign up to set email alerts
|

Diary Keeping in Writing Education

Abstract: One of the many types of texts that can be used in writing education is the diary. In this study, the opinions of the Turkish language teacher candidates about diary keeping and their diaries kept for two months in which they could freely express their thoughts were analyzed. It is a qualitative study in which thirty-four participants' diaries were examined, and semi-structured interviews were conducted with seventeen randomly selected candidates. It is observed that the topics dealt by the teacher candidates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 12 publications
1
6
0
3
Order By: Relevance
“…Based on our above findings, Lana showed that she generally used her diary to do the reflective practice. This finding confirms the previous studies mentioning the similar case in which diary writing help learner do reflective practice (Booud, 2001;Dincel & Savur, 2019;Hiemstra, 2001;Jarvis, 2001;Klimova, 2015;Rodgers, 2001).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Based on our above findings, Lana showed that she generally used her diary to do the reflective practice. This finding confirms the previous studies mentioning the similar case in which diary writing help learner do reflective practice (Booud, 2001;Dincel & Savur, 2019;Hiemstra, 2001;Jarvis, 2001;Klimova, 2015;Rodgers, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Some previous studies explained that diary writing helped learners' writing ability through building the habit of writing regularly (Dincel & Savur, 2019;Hiemstra 2001;Taqil et.al., 2015). The studies, however, did not mention particular abilities that helped learners in developing their writing skills.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations